Investigation of airflow and particle behavior around a subway train running in the underground tunnel. Issue 7 (2nd July 2016) - Lee, Kyung-Ran; Kim, Won-Geun; Woo, Sang-Hee; Kim, Jong Bum; Bae, Gwi-Nam; Park, Hyung-Koo; Yoon, Hwa Hyeon; Yook, Se-Jin
ABSTRACT: Airflow around an eight-passenger-car subway train running in the underground tunnel at a cruise speed of 70 km/h was numerically simulated, and the trajectories of the particles that were assumed to be re-suspended from the ground or generated at the contact points between the wheels and rails were predicted. In addition, field experiments were conducted to measure airflow velocity and PM10 mass concentration under a T-car (trailer car without a driving cab) during the running of a subway train in straight sections of the underground tunnel of the Seoul Subway Line 5. The numerically predicted airflow velocities agreed well with the experimental data with the error of less than 30%, and the predicted particle distribution showed a similar tendency to the experimental results. The airflow under the T-car was predicted to be relatively uniform compared to the airflow under other passenger cars. Both numerical results and experimental data signified that a lot of particles could drift under the T-car by showing a higher particle concentration in the central area of the space under the T-car than in the edge area. As a result, the space underneath the T-car is anticipated to be a good place for installing a dust-removal system. © 2016 American Association for Aerosol Research